Foodscapes and the resurgence of sinologism: Chinese dietary and medicinal practices in Peter Hessler’s works - Hao Ming; Shanthini Pillai (Penerbit Universiti Kebangsaan Malaysia, 2025)
When the consumption of food items emerges from perspectival constructs, they become foodscapes, and not merely food, transported by and through historical, linguistic, and political contexts. At the onset of the COVID-19 pandemic, Western media scapegoated Chinese dietary practices, reinforcing entrenched Orientalist perspectival constructs as an inner logic. This paper argues that such predispositions towards Chinese foodscapes can best be understood through a framework of Sinologism and the cultural unconscious as proposed by Mingdong Gu. To illustrate this, we use selected samples on Chinese dietary and medicinal practices in the works of Peter Hessler, an American writer widely acknowledged for countering American Orientalist biases in his narratives on China. How did Hessler respond to the central role that was accorded to China, the Chinese people and Chinese foodscapes? In what ways did the historically embedded stereotypes travel back from an Orientalist past to the globalised present? What implications does this have for balanced cross-cultural American engagements with China and its people? Our findings reveal that there is a strong tension between his effort to challenge Western media depictions of China and his own Orientalist bias, especially considering the prominent role of foodscapes and discussions about China and the Chinese in shaping narratives around the cause of the 2020 pandemic. We conclude that the inner logic of Sinologism is so strong that even a writer like Hessler is not immune to its influence, then balanced cross-cultural engagement in the Anglophone American context remains a persistent challenge.